Environmental discourses in public and international law - Jessup, Brad , 1978-; Rubenstein, Kim (Connecting international law with public law, 2012)
"The world is talking, pondering, and strategising about the environment. Ever more of the environment has been identified, publicly contemplated, or designated for despoliation and resource extraction. Remote and ?wild? places like the rugged Australian Kimberley and the far reaches of North America are now subject to advanced plans for fossil fuel extraction. Environmental disasters, including fires, floods, cyclones, earthquakes and tsunami, and schemes to alleviate or prevent future human suffering from catastrophe, have occupied governmental and organisational attention. Meanwhile, concerns about environmental degradation, and in particular human-induced climate change, dominate Western media and national and international politics, and are connecting communities through conversation and localised action. The nature, breadth and extent of global responses to climate change are also points of contention between the developing and developed worlds" -- Provided by publisher